Rethinking Muhammadiyah: Masjid, Teologi Dakwah Dan Tauhid Sosial (Perspektif Filsafat Dakwah) - Robby H. Abror (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2012)
As a dakwah movement that has a social ideals to bring the genuine Islamic community is the basic philosophical of Muhammadiyah’s movement. There are three important concepts such as, the movement of jama’a, qaryah tayyibah and sakinah family. Then came the strategy of "cultural da’wah" and look at the reality of the importance of greeting compound. In addition, the need to emphasize the contemporary missionary preaching bi al-kitâbah, in addition to bi-lisân al-hâl. Brilliant thinking regarding the function and existence redefined mosque, theology, preaching and social monotheism is needed to revitalize the spirit of the mission within the framework of philosophical-rational.